2018
DOI: 10.1080/00480169.2018.1509741
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intramammary infection status at drying off using indirect testing of milk samples

Abstract: AIMS To evaluate the Rapid Mastitis test (RMT, or California Mastitis test) and electrical conductivity (EC) at drying off when used alone or in combination with herd test data (maximum or last herd test somatic cell counts (SCC) before drying off), to define cows or quarters with intramammary infection, using microbiological culture as the gold standard. METHODS Quarter-level milk samples (n=609) from clinically healthy cows (n=153), in three herds in the Waikato region of New Zealand, were tested at drying o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…Additionally, however, freezing of milk samples is commonplace in many studies on IMI. Milk sample contamination or false-positive results can occur easily on farm, with contamination rates ranging from 2.3 to 6.6% in other studies (Gohary and McDougall, 2018;Naqvi et al, 2018). In the present study, the contamination rate in group 4, the group that followed NMC teat preparation guidelines, was slightly higher than in previous reports, with a contamination rate of 10%.…”
Section: Discussioncontrasting
confidence: 70%
“…Additionally, however, freezing of milk samples is commonplace in many studies on IMI. Milk sample contamination or false-positive results can occur easily on farm, with contamination rates ranging from 2.3 to 6.6% in other studies (Gohary and McDougall, 2018;Naqvi et al, 2018). In the present study, the contamination rate in group 4, the group that followed NMC teat preparation guidelines, was slightly higher than in previous reports, with a contamination rate of 10%.…”
Section: Discussioncontrasting
confidence: 70%
“…Another potential source of variability in responses to algorithm-guided SDCT is the algorithm itself. Many algorithms have been recommended by mastitis experts (Bradley et al, 2018;Gohary and McDougall, 2018;Vasquez et al, 2018), which use as few data points as possible (typically using only SCC and clinical mastitis data), to facilitate implementation under farm conditions. In the study by Scherpenzeel et al (2014), the SCC component of Non-inferiority analysis of dry period IMI cure risk for 2 selective dry cow therapy programs (SDCT), as compared with blanket dry cow therapy.…”
Section: Algorithm-guided Sdctmentioning
confidence: 99%
“…To our knowledge, no algorithm-guided SDCT trials have compared effects of different SCC cut points on measures of udder health. However, many algorithms with different SCC thresholds have been evaluated in their ability to predict IMI at dry-off (Pantoja et al, 2009;Gohary and McDougall, 2018;Lipkens et al, 2019). A recent multi-herd study in Belgium concluded that a single algorithm was unlikely to be highly accurate for all cows, and that other variables, such as herd-level estimates of subclinical mastitis prevalence, cow milk yield, and parity, should be incorporated into more sophisticated algorithms.…”
Section: Algorithm-guided Sdctmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested to use at least one record within 90 d of drying off to identify cows more likely to contract mastitis in the periparturient period (Green et al, 2007). Gohary and McDougall (2018) found that a single herd test in late lactation was as useful as multiple tests across the lactation as a predictor of IMI at drying-off.…”
Section: Animal Identification For Treatment Allocationmentioning
confidence: 99%